Sensory stimulations on food-related and social judgements - Choy, Melissa Min Er (2017)
Existing literature established that physical and social characteristics typical of crowded environments (Wansink, 2004) are associated with greater food consumptions but the direct effects of crowdedness on eating behaviour remains largely unclear. Given that mood also influences food intake (Macht, Roth, & Ellgring, 2002), it is hypothesized that individuals in crowded conditions will tend to select larger food portions than individuals in uncrowded conditions, even after controlling for the effects of mood (Hypothesis 1). Additionally, since crowdedness is associated with lowered construal levels which is in turn, linked with weaker self-control, it is also posited that lowered construal level mediates the relationship between high crowd level and larger food portion selection (Hypothesis 2). One hundred and thirty two participants (43 males, mean age = 21.27 years) from Nanyang Technological University were recruited. Audio recordings (socially-crowded setting or non-social noise) presented to participants and the number of participants present during each session were manipulated across the three conditions (crowded, uncrowded, control). Findings rendered limited support to both hypotheses. However, a gender effect was observed only within the crowded condition where males selected significantly larger food portions than females on a portion selection task. Therefore, future health intervention strategies targeted at promoting healthy eating should consider the difference in eating behaviours displayed by both genders in crowded environments.